2009
DOI: 10.3937/kampomed.60.167
|View full text |Cite
|
Sign up to set email alerts
|

A Case with Lumber Spinal Canal Stenosis Successfully Treated with Kigikenchutokauzu

Abstract: We report on a patient with residual complaints after an operation for lumber canal stenosis, successfully treated with the Kampo medicine, kigikenchutokauzu. The patient was 69 year-old woman complaining of severe coldness, numbness, and bilateral leg pain. She was diagnosed as having spinal canal stenosis when she was 67 years of age. Posterolateral fusion with laminectomy was performed at the age of 69, although severe coldness, numbness, and pain persisted even after her surgery. Also, her sutures had not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Patients often suffer from residual symptoms after operations for spinal diseases. Ogawa et al reported a case of postoperative residual pain, coldness, and numbness treated with Kampo medicine ( 99 ).…”
Section: Kampo Medicine For Gsmentioning
confidence: 99%
“…Patients often suffer from residual symptoms after operations for spinal diseases. Ogawa et al reported a case of postoperative residual pain, coldness, and numbness treated with Kampo medicine ( 99 ).…”
Section: Kampo Medicine For Gsmentioning
confidence: 99%